Onomatopoeia Variation Among Cultures: An Exploration in Selected Children’s Story Books - Syahruni Junaid; Ahmad Muzzammil; Aan Mujizat; Citra Andini (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
This research is about onomatopoeia in children's books in each country, the differences in the use of onomatopoeia in children's books from various countries also reflect the rich linguistic and cultural diversity throughout the world. The sounds perceived and expressed by children from various cultures reflect the unique ways of the societies in perceiving and interacting with the world around it. This research aimed to reveal onomatopoeia in children's storybooks, and analyze how onomatopoeia is used in storybooks from different cultures among countries in different continents. This research used a qualitative descriptive method. The results of this research revealed the types of onomatopoeia in children's storybooks in different countries and how it occured, as well as providing insight into linguistic and cultural diversity in children's literature around the world and how it reflects children's unique views and interactions  surrounding environment.